Formulation of Transparent Solid Soap Using Aloe Vera Leaf Flesh (Aloe vera (L.) Burm.f.) as Antioxidant - Ritonga, Oktavia; Lubis, Minda Sari; Dalimunthe, Gabena Indrayani; Yuniarti, Rafita (Pustaka Media Publishing, 2024)
Aloe vera is a plant whose components have many benefits, aloe vera also functions as an antioxidant that can ward off free radicals. The purpose of this study was to determine transparent soap with variations in aloe vera concentration that meet the physical quality of transparent soap and to determine antioxidant activity after formulation. This research uses an experimental method. In this study, aloe vera was formulated in the form of transparent soap. The physical evaluation carried out includes organoleptic test, water content test, pH test, foam height test and antioxidant activity test. Based on the results of the study it is known that. Antioxidant activity test of aloe vera leaf meat has antioxidant activity classified as moderate with IC50 108 µg/ml, while the activity of transparent soap using aloe vera has antioxidant activity classified as very weak with IC50 obtained for F0 of 980.2290, F1: 482.3775, F2: 464.7310, F3: 407.5596 µg/ml. The conclusion of this study is that transparent soap using aloe vera meets the requirements of visual quality evaluation according to SNI and has antioxidant activity with a very weak category.